PENGARUH MODEL PROBLEM BASED LEARNING DENGAN STRATEGI METAKOGNITIF TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR SISWA TAHUN AJARAN 2021/2022 - Perayanti Sinaga, Dian; Tridelpina Purba, Sumarny; Apsari Rahayu, Dinda (Jurnal Metabio, 2022)
This study aims to examine the effect of the Problem-Based Learning Model with Metacognitive Strategies on Critical Thinking Skills and Student Learning Outcomes. This study is a quantitative study. The study population consisted of 120 students consisting of 4 classes. Sampling was carried out by Cluster Random Sampling, namely class VIII-A using Problem-Based Learning with Metacognitive Strategies and VIII-B using the lecture method with 30 students in each class. The research instrument used tests and questionnaires. Based on the results of hypothesis testing using the t-test, as obtained thitung 6.836 > ttabel (1.701) at a significance level of 0.000 < 0.05. Based on this, it can be concluded that the Sig. value < 0.05 and thitung value > ttabel, which means H_0 is rejected and 〖H〗_a is accepted. Thus, there is a significant influence between the grades in the experimental class and the grades in the control class. Based on the results of the hypothesis testing using the F-test, the calculated F value is greater than the F-table (9.709 > 4.004) and the sig. value is less than 0.05 (0.003 < 0.05). Thus, Ha is accepted and H0 is rejected, indicating a significant effect of using the Problem-Based Learning model with metacognitive strategies on critical thinking. The study concluded that using the Problem-Based Learning model has an impact on critical thinking skills and learning outcome students of Prama Artha Private Middle School in the 2021/2022 academic year.